Gene loss during a transition to multicellularity - Berenice Jiménez-Marín; Jessica B. Rakijas; Antariksh Tyagi; Aakash Pandey; Erik R. Hanschen; Jaden Anderson; Matthew G. Heffel; Thomas G. Platt; Bradley J. S. C. Olson (Scientific Reports, 2023)
Abstract Multicellular evolution is a major transition associated with momentous diversification of multiple lineages and increased developmental complexity. The volvocine algae comprise a valuable system for the study of this transition, as they span from unicellular to undifferentiated and differentiated multicellular morphologies despite their genomes being similar, suggesting multicellular evolution requires few genetic changes to undergo dramatic shifts in developmental complexity. Here, the evolutionary dynamics of six volvocine genomes were examined, where a gradual loss of genes was observed in parallel to the co-option of a few key genes. Protein complexes in the six species exhibited novel interactions, suggesting that gene loss could play a role in evolutionary novelty. This finding was supported by gene network modeling, where gene loss outpaces gene gain in generating novel stable network states. These results suggest gene loss, in addition to gene gain and co-option, may be important for the evolution developmental complexity.